Empirical Review of Foreign Finance and SMEs Performance in Lagos State Nigeria - Hector Onyekachi , Ekeocha; Mejabi, Folorunsho; Orisanwo, Israel (Management Analytics and Social Insights, 2025)
This study explored the empirical review on the effect of foreign finance on the performance of Small and Medium Enterprises (SMEs) in Nigeria, building on previous works of literature. The review uncovered the methodologies and theories used and the findings of various studies. The researcher observed from empirical reviews of literature that the conclusions of the subject matter remain inconclusive. There were conflicting findings in the various studies carried out by different researchers. Beyond finance, other factors contribute to SMEs' performance, which should be controlled. Such factors include firm age, size, and the experience of the manager. Many of the literature reviewed have no control variable. Few studies introduced some control variables but discovered the presence of heterogeneous effects concerning the firm size, firm age, region, industry, and intensity of public support, thus requiring more studies that would address the long-term effects of foreign finance on SMEs. Future studies should introduce a control variable, namely, firm size. Control variables help in achieving consistent and unbiased results. Much of the reviewed literature concentrated only on Foreign Direct Investment (FDI). The researcher has added other forms of foreign finance, including grants, foreign loans, funds from foreign Development Finance Institutions (DFI), and Venture Capital (VC). In Nigeria, there are few studies on VCs as the concept is still evolving. The VCs reinforced the theoretical gap that future studies should fill. Researches backed by theories enjoy an added layer of credibility and support. A good number of reviewed studies were not backed by any theory; as a result, future studies should consider the pecking order theory and the theory of performance.